Klippel-Feil Syndrome and Dextrocardia: A Case Report - Erkan Kaya,; Ali Hikmet Kayar,; Selahattin Özyürek,; Memduh Dursun, (Archives of Rheumatology, 2009)
Klippel-Feil syndrome is a congenital malformation that exists because of a failure of the normal segmentation of cervical somites during the third and eighth weeks of gestation. The classical triad includes short neck, low hair line, restriction in neck motion, and fusion of at least two cervical segments. Patients with Klippel-Feil syndrome usually present with the disease during childhood but may present later in life. In this case report, we present a 17-year-old female patient with cervical vertebra anomalies, scoliosis, Sprengel's deformity, dextrocardia, and costa anomalies (13 costa on the right side and 11 costa on the left side). (Turk J Rheumatol 2009; 24: 163-5)